2017
DOI: 10.1016/j.physbeh.2016.11.014
|View full text |Cite
|
Sign up to set email alerts
|

A users guide to HPA axis research

Abstract: Glucocorticoid hormones (cortisol and corticosterone - CORT) are the effector hormones of the hypothalamic-pituitary-adrenal (HPA) axis neuroendocrine system. CORT is a systemic intercellular signal whose level predictably varies with time of day and dynamically increases with environmental and psychological stressors. This hormonal signal is utilized by virtually every cell and physiological system of the body to optimize performance according to circadian, environmental and physiological demands. Disturbance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
197
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 302 publications
(214 citation statements)
references
References 278 publications
(293 reference statements)
13
197
0
4
Order By: Relevance
“…The CORT-induced increase in Sgk1 mRNA was similar at both times of day. As expected, CORT treatment produced relatively high levels of plasma CORT 30 min after injection that were in the high physiological stress range [17], and these circulating levels were similar at both times of day.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…The CORT-induced increase in Sgk1 mRNA was similar at both times of day. As expected, CORT treatment produced relatively high levels of plasma CORT 30 min after injection that were in the high physiological stress range [17], and these circulating levels were similar at both times of day.…”
Section: Resultssupporting
confidence: 63%
“…Rats were acclimated to lighting conditions at the University of Colorado Boulder animal facility for two weeks before undergoing ADX surgery during the second half of the light phase. For three days after surgery, CORT (25 μg/ml; Steraloids Inc., Newport, RI) was replaced in the post-operative drinking water (tap water containing 0.1% ethanol, 0.9% saline, and 0.04% ibuprofen (Pfizer, Madison, NJ)) during the first two hours of the dark phase in order to preserve diurnal variations in baseline CORT levels [17]. On the third day after surgery, rats received no injection, vehicle injection (10% ethanol, 30% propylene glycol, 60% sterile saline, 1 ml/kg i.p.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To do this, samples were immersed in a 75 °C water bath for 60 min. Prior assays conducted within our laboratory have demonstrated that this procedure produces superior denaturation of CBG compared to the steroid displacemernt step provided in the kit (unpublished observations, as discussed in [39, 40]). This assay has been shown to have a sensitivity of 27.0 pg/ml, with an inter-assay coefficient of 5.40%.…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence linking AD progression with decreased variability in CBF [8] and increased variability in BP [9]. Glucocorticoid hormone levels vary in 24-h cycles and dynamically increase with stress [10,11]. Circadian rhythms of cortisol (a key glucocorticoid hormone) are associated with changes in heart rate [12,13] and BP.…”
Section: Introductionmentioning
confidence: 99%